p-integrable selectors of multimeasures - Richard Aló; Andre de Korvin; Charles E. Roberts, Jr. (International Journal of Mathematics and Mathematical Sciences)
The present work is a study of multivalued functions and measures which have many applications to mathematical economics and control problems. Both have received considerable attention in recent years. We study the set of selectors of the space of all p- integrable, X- valued additive set functions. This space contains an isometrically imbedded copy of Lp(X).